2013
DOI: 10.1111/bjh.12210
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and natural history of pure red cell aplasia in major ABO‐mismatched haematopoietic cell transplantation

Abstract: Summary Major ABO mismatching is not considered a contraindication to allogeneic haematopoietic stem cell transplantation (HSCT). Modern reduced-intensity conditioning and reduced-toxicity regimens cause much less myeloablation than conventional myeloablative regimens, such as cyclophosphamide with busulfan or total body irradiation, which may affect the incidence of pure red cell aplasia (PRCA). We estimated the incidence and described the natural history of PRCA in patients with major ABO-mismatched donor st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 24 publications
8
49
0
2
Order By: Relevance
“…Various treatment options have been reported for patients with PRCA after major ABO‐incompatible HSCT; however, no standard of care has been established so far . Our patient did not respond to several lines of treatment and eventually achieved resolution of PRCA after PEX, although a spontaneous resolution might have occurred, as described in some reports …”
Section: Discussionsupporting
confidence: 50%
“…Various treatment options have been reported for patients with PRCA after major ABO‐incompatible HSCT; however, no standard of care has been established so far . Our patient did not respond to several lines of treatment and eventually achieved resolution of PRCA after PEX, although a spontaneous resolution might have occurred, as described in some reports …”
Section: Discussionsupporting
confidence: 50%
“…Most studies have reported that PRCA resolves spontaneously or after reduction of immunosuppression . Other treatments tried by other studies include RTX, PLX, and DLI, although with inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…An investigation into red cell aplasia, for transplants performed between 2007 and 2008, identified 27% of patients received major ABOi transplants and 7.5% of these major ABOi transplanted patients developed PRCA (Aung et al ., ). Chimerism studies for T‐cell and myeloid cell lineage and time to engraftment for neutrophil and platelets did not differ significantly for the major ABOi patients that did, and did not develop PRCA.…”
Section: Non‐hla Factors To Be Considered For Related and Unrelated Dmentioning
confidence: 97%